PENERAPAN MODEL PROBLEM BASED LEARNING DENGAN PENDEKATAN BERDIFERENSIASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN KIMIA KELAS X SMA 6 MATARAM - Oni Pahdianti; Yunita Arian Sari Anwar; Baiq Sri Ayu Husniarti; Nyoman Martha Jayanthi Lembayung (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2023)
This study aims to see whether the application of the Problem Based Learning Model with a Differentiated Approach can improve the learning outcomes of students in class X9 SMAN 6 Mataram in the 2022/2023 school year in chemistry subjects. The type of research used is Classroom Action Research (PTK) which is cooperation (collaboration) between researchers, teachers and supervisors who are divided into three cycles. Each cycle consists of planning, implementation and reflection. The results of the research carried out on 36 students, namely in the first cycle the learning outcomes were very low with the average obtained was 28.61 with the number of students who reached the KKM only 6 out of 36 students with KKM of 75 so that only 16.67% could reach KKM. In the second cycle the average score of students was 71.53 with the number of students who reached completeness was 24 people, the percentage of completeness was around 66.67%. In the third cycle the average learner learning outcomes obtained were 76.94 with the number of students who completed were 25 students out of 36 people with a percentage of completeness of 72.22%. So, it can be said that the Porblem Based Leaning Model (PBL) with a differentiated approach can improve student learning outcomes in Chemistry subjects.